How Europe underdeveloped Africa - Rodney, Walter (Washington, D.C. : Howard University Press, 2009)
Examines the causes for the underdevelopment of Africa, tracing events from before the coming of the Europeans in the fifteenth century through the colonial period, and argues that the problem is a direct result of the imperialist system and the European capitalists who manipulated that system.
Second printing.